Chemotherapy and radiotherapy in locally advanced head and neck cancer: an individual patient data network meta-analysis. Issue 5 (May 2021) - Petit, Claire; Lacas, Benjamin; Pignon, Jean-Pierre; Le, Quynh Thu; Grégoire, Vincent; Grau, Cai; Hackshaw, Allan; Zackrisson, Björn; Parmar, Mahesh K B; Lee, Ju-Whei; Ghi, Maria Grazia; Sanguineti, Giuseppe; et al.
Summary: Background: Randomised, controlled trials and meta-analyses have shown the survival benefit of concomitant chemoradiotherapy or hyperfractionated radiotherapy in the treatment of locally advanced head and neck cancer. However, the relative efficacy of these treatments is unknown. We aimed to determine whether one treatment was superior to the other. Methods: We did a frequentist network meta-analysis based on individual patient data of meta-analyses evaluating the role of chemotherapy (Meta-Analysis of Chemotherapy in Head and Neck Cancer [MACH-NC]) and of altered fractionation radiotherapy (Meta-Analysis of Radiotherapy in Carcinomas of Head and Neck [MARCH]). Randomised, controlled trials that enrolled patients with non-metastatic head and neck squamous cell cancer between Jan 1, 1980, and Dec 31, 2016, were included. We used a two-step random-effects approach, and the log-rank test, stratified by trial to compare treatments, with locoregional therapy as the reference. Overall survival was the primary endpoint. The global Cochran Q statistic was used to assess homogeneity and consistency and P score to rank treatments (higher scores indicate more effective therapies). Findings: 115 randomised, controlled trials, which enrolled patients between Jan 1, 1980, and April 30, 2012, yielded 154 comparisons (28 978 patients with 19 253 deaths and 20 579 progression events). Treatments were grouped into 16 modalities, for which 35 types of direct comparisons were available. Median follow-up based on all trials was 6·6 years (IQR 5·0–9·4). Hyperfractionated radiotherapy with concomitant chemotherapy (HFCRT) was ranked as the best treatment for overall survival (P score 97%; hazard ratio 0·63 [95% CI 0·51–0·77] compared with locoregional therapy). The hazard ratio of HFCRT compared with locoregional therapy with concomitant chemoradiotherapy with platinum-based chemotherapy (CLRTP ) was 0·82 (95% CI 0·66–1·01) for overall survival. The superiority of HFCRT was robust to sensitivity analyses. Three other modalities of treatment had a better P score, but not a significantly better HR, for overall survival than CLRTP (P score 78%): induction chemotherapy with taxane, cisplatin, and fluorouracil followed by locoregional therapy (ICTaxPF -LRT; 89%), accelerated radiotherapy with concomitant chemotherapy (82%), and ICTaxPF followed by CLRT (80%). Interpretation: The results of this network meta-analysis suggest that further intensifying chemoradiotherapy, using HFCRT or ICTaxPF -CLRT, could improve outcomes over chemoradiotherapy for the treatment of locally advanced head and neck cancer. Fundings: French Institut National du Cancer, French Ligue Nationale Contre le Cancer, and Fondation ARC.